2015
DOI: 10.4244/eijv11i3a57
|View full text |Cite
|
Sign up to set email alerts
|

Geographic miss with aorto-ostial coronary stent implantation: insights from high-resolution coronary computed tomography angiography

Abstract: Geographic miss was common in aorto-ostial stenting and was underestimated by conventional two-dimensional angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Also, ultrasound guidance for stent placement has been associated with better outcomes [10,15]. This effect on outcomes may be explained by the ability of IVUS to reduce geographical miss, whereas two-dimensional angiography frequently does not result in complete lesion coverage [16]. Therefore, routine use of IVUS in aorto-ostial lesions should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Also, ultrasound guidance for stent placement has been associated with better outcomes [10,15]. This effect on outcomes may be explained by the ability of IVUS to reduce geographical miss, whereas two-dimensional angiography frequently does not result in complete lesion coverage [16]. Therefore, routine use of IVUS in aorto-ostial lesions should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…6A, B ). In one short series of patients after LM stenting, control MSCT revealed that the stent had been implanted optimally in relation to the ostium only in 3 out of 23 cases [ 5 ]. The precise positioning of stents in the coronary ostia is of paramount importance because it can substantially affect long-term clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…The gap results partly from differences in the plaque composition, which is more rigid, calcified, and bulky in the case of AOL [ 3 , 4 ]. A lot of target lesion failures are due to technical problems during the procedure, resulting in overly deep stent implantation and incomplete coverage of the treated lesion [ 5 ]. On the other hand, excessive protrusion of the stent into the aorta also has negative consequences because it can hinder re-engagement of the vessel with the catheter or seriously complicate subsequent interventions on the aortic valve [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The follow‐up results showed that stent mispositioning was associated with a significantly higher ISR and TLR compared to patients with accurate stent placement. Rubinshtein et al performed postoperative CCTA in patients with aorto‐ostial stenosis and found that the incidence of inaccurate stent placement was 87.00%, of which 40.00% were closely related to the techniques. Timurkaynak et al used the draw‐back technique for the accurate localization of LAD ostial lesions.…”
Section: Discussionmentioning
confidence: 99%